Retention rate in methadone maintenance treatment and factors associated among referred patients from the compulsory residential centers compared to voluntary patients - Radfar, Niayesh; Radfar, Seyed Ramin; Mohammadi, Faezeh; Azimi, Amir; Amirkafi, Ali; Tehrani-Banihashemi, Arash (Frontiers in Psychiatry, 2023)
Compulsory treatment has decades of history in Iran both before and after the Islamic revolution, but there are many debates regarding its efficacy and effectiveness. One of the indices that can be used for the estimation of the efficacy of treatment methods is retention rate. This study is going to explore factors influencing retention rate among patients referred from compulsory treatment centers compared to those who are coming by their own intention. This study is a retrospective (historical) cohort study that has been conducted among patients who are taking methadone maintenance treatment (MMT). The study sample were selected from the MMT centers that accept both the referral patients from the center of Article 16 (compulsory) and voluntary patients. All newly admitted patients from March 2017 to March 2018 were enrolled in the study and followed up until March 2019. The collected data are analyzed descriptively and analytically using SPSS software version 26 with appropriate statistical tests. A total of 105 participants were recruited for the study. All male with a mean age of 36.6 ± 7.9 years. 56% of individuals were referred from article 16 campus. One-year retention rate was 15.84. One-year retention rate for the patients who were referred from article 16 campus was 12.28 and for non-referred patients it was 20.45 (P value = 0.128). Among the other studied factors only marital status was significantly associated with MMT retention (P = 0.023). Some studies found a better retention rate in treatment for the clients that take treatment on their own demand compared to those who are taking treatment as a compulsory option. , Although the average of being in treatment were about 60 days higher than those referred from compulsory settings, but this study did not find any significant differences in terms of retention days and a one-year retention rate. Further studies with larger sample size and longer follow-up are needed to explore the efficacy of compulsory treatment methods in Iran.